The Effect of Professional Skepticism and Red Flags on Fraud Detection with Auditor Experience as a Moderating Variable - Kiara Niko Putri; Ghina Rafifah Rafifah (Yayasan Az Zukhruf Cendikia, 2025)
Purpose–This study aims to analyze the influence of professional skepticism, and red flags on fraud detection with auditor experience serving as a moderating variable. The research highlights the critical importance or adopting professional skepticism, identifying red flags, and leveraging auditor experience to enhance the effectiveness of fraud detection. Design/methodology/approach–The research uses quantitative methods with a correlational approach. This study uses a questionnaire distributed to KAP and students who have taken audit courses. A total of 39 questionnaires were distributed through social media platforms, containing 39 statements that respondents had to answer. Of these, 39 responses were received, which came from 5 regions. To analyze the data and obtain results, the study used PLS-SEM Version 3.0. Findings–This study examines the impact of professional skepticism and red flags on fraud detection, with auditor experience as a moderating variable. Data were collected from 39 auditors and students with audit experience and analyzed using Partial Least Square (PLS) with Moderated Regression Analysis. The results how that professional skepticism positively and significantly influences fraud detection, while red flags have a positive but significant effect. Additionally, auditor experience does not strengthen the relationship between professional skepticism, red flags, and fraud detection. The findings suggest the need for ongoing auditor training and a stronger emphasis on skepticism in audit practices Research limitations/implication s–Lies in its focus understanding the relationship between professional skepticism and red flags on fraud detection, by considering the role of auditor experience as a moderating professional skepticism and identifying red flags in supporting the effectiveness on fraud detection, although the role of auditor experience as moderating does not provide significant results.